The Functional Role of PRC2 in Early T-cell Precursor Acute Lymphoblastic Leukemia (ETP-ALL) – Mechanisms and Opportunities - Bernt, Kathrin M.; Hunger, Stephen P.; Neff, Tobias (Frontiers in Pediatrics, 2016)
Early T-Cell Precursor Acute Lymphoblastic Leukemia (ETP-ALL) is a relatively newly identified subset of T-lineage ALL. There are conflicting results regarding prognosis, and the genetic basis of this condition is variable. Here we summarize the current status of the field and discuss the role of mutations in the Polycomb Repressive Complex 2 frequently identified in ETP-ALL patients.